Detection Of Escherichia Coli Virulence Genes ( Pap , Afa , Iha Ipr2 And Hly ) Isolated From Patients With Urinary Tract Infections In Babylon Province, Iraq - Kadhim, Iman J; Hawani, Israa Abed Ali Al (South Eastern European Journal of Public Health, 2024)
The current study included a collection of 110 urine samples of both sexes of different ages for patients with urinary tract infections, who consulted Al-Hilla Teaching Hospital and the Children and Maternity Hospital in Al-Hilla city, through the period from May 2020 to December 2020, to investigate some virulence factors associated with Escherichia coli bacterium. The results of the biochemical tests revealed that 74 (67.3%) isolates were belonging to E. coli that was isolated from the urine samples. The results also indicated that the females were more infected 47 (63.5 %) with urinary tract infections than males 27 (36.4 %). Some virulence factor genes have also been investigated using the polymerase chain reaction (PCR) technique, which are (pap, afa, iha, ipr2 and hly genes). The PCR results for E.coli genes revealed that, 11 isolates contain pap gene (7 ( 14.8 %) and 4 ( 14.8 %)), while 9 isolates possesses afa gene ( 6 ( 12.7 %) and 3 ( 11.1 %)), whereas 5 isolates have gene iha (3 ( 6.3 %) and 2 ( 7.4 % )) , In addition to 30 isolates have irp2 gene (21 ( 44.6 % ) and 9 ( 33.3 % )) and 27 isolates contain hly gene ( 19 ( 40.4 %) and 8 ( 29.6 %)). These percentages are for females and males respectively. Conclusions: E.coli is the bacterium that dominant the UTIs. Females are more likely to develop UTIs than males. The irp2 gene responsible for taking iron is the most genetically studied genome that causes UTIs, followed by the gene hly responsible for producing α-hemolysin enzyme second among the gene of the virulence factors under study.